PERBANDINGAN HASIL PEMERIKSAAN KONTAMINASI BAKTERI PADA PRODUK TROMBOCYTE CONCENTRATE METODE KONVENSIONAL DAN APHERESIS - Resti Ariani; Ria Aidina (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2022)
Platelet Concentrate (PC) is one of the blood products that is often used for transfusion. The storage temperature for TC products is in the range of 20-24OC which is the optimal temperature for bacterial growth. TC products contaminated with bacteria can cause a dangerous septic reaction. With the development of blood transfusion, apheresis methods emerged for the manufacture and aseptic collection of TC products. The apheresis method is considered safer than the conventional method which has a high chance of bacterial contamination. This study aims to compare the results of the examination of bacterial contamination in conventional TC products and apheresis methods. This study is a comparative descriptive study with a retrospective approach in the form of examining data on bacterial contamination of TC PMI Semarang City during 2019. The results of the examination of the TC apheresis method product showed that there were no TC products that were contaminated with bacteria (0.0%; 0 of 48), while in conventional method, there is 1 TC product that has bacterial contamination (0.3%; 1 out of 360). Fisher exact test on each TC product obtained p value = 1.00 (> 0.05) so that the difference that appears is not significant. Examination of bacterial contamination in conventional TC products and apheresis gave the same good results.